"Blowing in the wind": a review of teenage smoking. Issue 1 (3rd September 2007) - Lenney, W; Enderby, B
Abstract : One quarter of all adults in the UK are regular smokers, the vast majority having started smoking in their teens. Teenage smoking, especially in females, continues to increase both as regards the numbers of cigarettes smoked and the numbers of teenagers who regularly smoke. The main factors influencing teenagers to smoke are peer pressure, family members who smoke and experimentation. Nicotine dependence can develop very quickly and in the UK little attention has been directed towards helping teenagers break the habit. In global terms the figures are frightening. Of the 1.25 billion smokers, 800 million live in developing countries. In the UK, government legislation, restrictions on advertising and educational programmes may improve the situation in the near future but there is still little recognition that smoking is responsible for 4 million deaths each year worldwide and insufficient attention has been paid to children and young families to try to prevent children and teenagers from smoking in the first place.